Indium hydroxide nanocubes and microcubes obtained by microwave-assisted hydrothermal method - Motta, F. V. [UNESP]; Lima, R. C.; Marques, A. P. A.; Li, M. S.; Leite, E. R.; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Elsevier B.V. Sa, 2010)
Single crystalline indium hydroxide (In(OH)(3)) architectures were prepared by a rapid and efficient microwave-assisted hydrothermal (MAH) method using indium chloride as the precursor Nanostructures were obtained at a low temperature (140 degrees C with a time of 1 min) In(OH)(3) samples were prepared at the same temperature for 8 with a time of 64 min. Using this method, In(OH)3 samples were obtained at milder conditions of temperature and time compared to the conventional hydrothermal method Field emission scanning electron microscopy images confirm that these samples are composed of 3D nanocubic, microcubic and irregular structures of about 70 nm to 5 mu m in size. Fourier transform Raman spectroscopy and photoluminescence (PL) measurements were used to characterize the products (C) 2010 Elsevier B V. All rights reserved.
Keywords: Indium hydroxide; Microwave-Assisted Hydrothermal; Photoluminescence